2022
DOI: 10.3390/ani12192580
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of an Energy Consumption Model for Animal Houses Achieving Precision Livestock Farming

Abstract: Indoor environmental control is usually applied in poultry farming to ensure optimum growth conditions for birds. However, these control methods represent a considerable share of total energy consumption, and the trend of applying new equipment in the future for precision livestock farming would further increase energy demand, resulting in an increase in greenhouse gas emissions and management costs. Therefore, to ensure optimum efficiency of both energy use and livestock productivity, a customized hourly mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…However, despite its complexity, authors reported differences in output results between this new method and more sophisticated professional simulation tools [46][47][48]. Hence, it was decided to apply the simpler method of EN ISO 13790, still used in practice [49,50].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite its complexity, authors reported differences in output results between this new method and more sophisticated professional simulation tools [46][47][48]. Hence, it was decided to apply the simpler method of EN ISO 13790, still used in practice [49,50].…”
Section: Introductionmentioning
confidence: 99%